INTEGRASI BERPIKIR KRITIS DAN PEMECAHAN MASALAH DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) - Laila Rahmi Hasanah; Mona Alyaa Sausan; Lailatul Mukjizat; Kasinyo Harto; Irja Putra Pratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine how the integration of critical thinking and problem-solving skills can be operationalized in Islamic Religious Education (PAI) learning. This study uses a library research method by analyzing various relevant scientific literature sources. The results of the study indicate that critical thinking has a strong epistemological foundation in Islam, as reflected in the Quran and the thoughts of classical scholars such as Al-Ghazali, Ibn Khaldun, and Al-Farabi. The integration of critical thinking in PAI can be achieved through active learning, a contextual approach, and problem-based learning. The problem-solving method applied through the stages of problem classification, brainstorming, evaluation, and implementation has proven effective in training students to think systematically and responsibly in accordance with Islamic values. PAI educators play a strategic role as facilitators who create a dialogic and reflective classroom culture and utilize educational technology to strengthen students' analytical skills. This research is expected to serve as a reference for educators and researchers in developing PAI learning models that are not only cognitively oriented but also shape students' characters to be analytical, reflective, and able to face real-life challenges.